Moving targets a user's guide to British art now - Buck, Louisa (Tate Gallery Publ., 1997)
Item looks at the British art scene in the 1990s, including sections on artists (older generation, such as Bacon, Freud and Rego, as well as the younger ones, such as Hirst, Rae, Lucas etc.), dealers, patrons, commentators, art schools, prizes, publications, and venues.
Keywords: Geschichte 1900-2000; Geschichte 1950-1997; Art - 20e siècle - Grande-Bretagne; Art - Grande-Bretagne; Kunst; Art, British -- 20th century; Großbritannien; Enzyklopädie